EASL versus LI-RADS: Intra-individual comparison of MRI with extracellular contrast and gadoxetic acid for diagnosis of small HCC - Min, Ji Hye; Kim, Jong Man; Kim, Young Kon; Kim, Honsoul; Cha, Dong Ik; Kang, Tae Wook; Choi, Gyu Seong; Choi, Seo Youn; Ahn, Soohyun (Liver International, 2021)
Background & Aims: Liver Imaging Reporting and Data System (LI-RADS) and European Association for the Study (EASL) criteria for hepatocellular carcinoma (HCC) diagnosis have been updated in 2018. We aimed to compare the HCC diagnostic performance of LI-RADS and EASL criteria with extracellular contrast agents-MRI (ECA-MRI) and hepatobiliary agents-MRI (HBA-MRI). Methods: We prospectively evaluated 179 participants with cirrhosis (n = 105) or non-cirrhotic chronic hepatitis B (CHB) (n = 74) who underwent both ECA-MRI and HBA-MRI before surgery for de novo nodule(s) measuring 10-30 mm. We compared the HCC diagnostic performance of EASL and LR-5 in both MRIs. Results: In an analysis of 215 observations (175 HCCs, 17 non-HCC malignancies and 23 benign lesions) identified from cirrhotic or non-cirrhotic CHB participants, LR-5 with ECA-MRI provided the highest sensitivity (80.7%), followed by EASL with ECA-MRI (76.2%), LR-5 with HBA-MRI (67.3%) and EASL with HBA-MRI (63.0%, all P <.05). The specificities were comparable (89.4%-91.5%). When the analysis is limited to participants with pathological cirrhosis (123 observations), the sensitivity of LR-5 with ECA-MRI was similar to that of EASL with ECA-MRI (82.7% vs 80.2%, P =.156), but higher than LR-5 with HBA-MRI (65.1%) or EASL with HBA-MRI (62.8%, both P <.001), with comparable specificities (87.5%-91.7%). Conclusions: The LR-5 with ECA-MRI yielded the highest sensitivity with a similar specificity for HCC diagnosis in cirrhosis and non-cirrhotic CHB participants, while the sensitivities of LR-5 and EASL with ECA-MRI are similar for cirrhosis participants. This indicates non-invasive diagnosis criteria can differ by contrast agents and presence of cirrhosis.
Keywords: Carcinoma, Hepatocellular; Contrast Media; Gadolinium DTPA; Humans; Liver Neoplasms; Magnetic Resonance Imaging; Retrospective Studies; Sensitivity and Specificity; contrast agent; EASL; hepatocellular carcinoma; LI-RADS; magnetic resonance imaging